Epidemiology of injuries in elite female futsal players: A prospective cohort study - Lago-Fuentes, C.; Jiménez-Loaisa, A.; Padrón-Cabo, A.; Calvo, M. M.; García-Pinillos, F.; Rey, E. (International Journal of Sports Medicine, 2020)
Injuries are one of the worst case scenarios for an athlete and a team. The aim of this study was to analyze the injury incidence, characteristics and burden among a cohort of elite female futsal players. A prospective cohort study was designed over a season. Eighty-nine players from seven elite female futsal teams were monitored during the whole season. Eight different variables were recorded when an injury happened, as well as exposure time. A total of 90 injuries were recorded so that 54 out of 89 players (60.6%) sustained an injury. The overall injury incidence was 5 injuries per 1000 h of futsal play exposure. Moderate injuries were the most frequent (1.7 injuries per 1000 h of futsal play exposure). The quadriceps and ankle were the regions where most injuries occurred. Contact injuries were more common during matches than training, and usually happened at the end of the season. Elite female futsal players are exposed to a substantial injury risk, especially on ankle and quadriceps with moderate severity, occurring at the end of the sessions, especially during matches. These results highlight the need of new preventive strategies to reduce the high injury incidence in female futsal players.